Structural basis for assembly of non-canonical small subunits into type I-C Cascade - O’Brien, Roisin E.; Santos, Inês C.; Wrapp, Daniel; Bravo, Jack P. K.; Schwartz, Evan A.; Brodbelt, Jennifer S.; Taylor, David W. (Nature communications, 2020)
Bacteria and archaea employ CRISPR (clustered, regularly, interspaced, short palindromic repeats)-Cas (CRISPR-associated) systems as a type of adaptive immunity to target and degrade foreign nucleic acids. While a myriad of CRISPR-Cas systems have been identified to date, type I-C is one of the most commonly found subtypes in nature. Interestingly, the type I-C system employs a minimal Cascade effector complex, which encodes only three unique subunits in its operon. Here, we present a 3.1 Å resolution cryo-EM structure of the Desulfovibrio vulgaris type I-C Cascade, revealing the molecular mechanisms that underlie RNA-directed complex assembly. We demonstrate how this minimal Cascade utilizes previously overlooked, non-canonical small subunits to stabilize R-loop formation. Furthermore, we describe putative PAM and Cas3 binding sites. These findings provide the structural basis for harnessing the type I-C Cascade as a genome-engineering tool. Type I-C Cascade (the CRISPR-associated complex for antiviral defense) is a minimal system, comprising only three unique Cas proteins. Cryo-EM structure of the Desulfovibrio vulgaris type I-C Cascade reveals the molecular mechanisms that underlie RNA-directed complex assembly.